CHANGES IN THE PREVALENCE OF DRUG RESISTANT TUBERCULOSIS - V. B. Galkin; S. A. Sterlikov; G. S. Balasanyants; P. K. Yablonsky (Туберкулез и болезни лёгких)
The tendency of tuberculosis prevalence reduction observed in the Russian Federation is mostly related to the cases without multiple drug resistance (MDR). In general the number of MDR TB cases still tends to be increasing in the Russian Federation. Confident long-term reduction is registered only in the Central and North-Western Districts with relatively low level of MDR TB prevalence. From 2017 MDR TB patients are expected to prevail in the structure of the sputum positive cases which surely provides negative impact on the treatment efficiency and epidemic trends. The system of dispensary follow-up allows evaluating the annual number of MDT TB cases and following the ways of its increase and reduction. Taking MDR TB sources on and off the register is less intensive compared to the same flows of non-MDR infectious cases. The number of MDR TB sources is increasing mostly due new tuberculosis cases however acquired MDR TB makes significant contribution to the growth of MDR TB sources number. The increase in the ratio of respiratory MDR TB patients with sputum conversion to those died reflects the success in the improvement of the treatment strategy of MDR TB patients.